Printed (2x1) patch array antenna at 2.45GHz / Sumayah Ilias and Aiza Mahyuni Mozi - Ilias, Sumayah; Mozi, Aiza Mahyuni
This paper proposed of a microstrip rectangular patch array antenna with operating frequency at 2.45GHz for WLAN application. The antenna array of 2x1 microstrip rectangular patch antenna with microstrip line feeding based on quarter-wave impedance matching technique was designed and simulated using CST Microwave Environment software. The performance of the designed antenna was analyzed in term of return loss, VSWR, bandwidth, directivity, radiation pattern and gain. The antenna was then fabricated on the substrate type FR- 4 with dielectric constant of 4.7 and thickness of 1.6mm respectively. The antenna was measured using Vector Network Analyzer (VN A) and the details of the proposed antenna design and simulation result for 2.45GHz WLAN band are promising. The return loss, sll for the single patch antenna and (2x1) array antenna are -12.938 and - 19.468 respectively. Other than that, the simulated bandwidth for the single patch antenna is 3.82%. Meanwhile for the (2x1) array antenna is 3.98%.This is proved that (2x1) array antenna is better than single patch antenna in term of wider bandwidth, higher gain and better directivity.